USE OF FABRICS WITH ENHANCED PERFORMANCE CHARACTERISTICS IN MANUFACTURING SPECIAL APPAREL FOR OIL AND GAS INDUSTRY WORKERS. (Multidisciplinary Journal of Science and Technology, 2024)
This article provides complete information on material selection, justification and materials for the production of special clothes. Information about the classification processes of special clothes according to their application is given.